The appropriate troponin T level associated with coronary occlusions in chronic kidney disease patients - Sittichanbuncha Y; Sricharoen P; Tangkulpanich P; Sawanyawisuth K (Dove Medical Press, 2015)
Yuwares Sittichanbuncha,1 Pungkava Sricharoen,1 Panvilai Tangkulpanich,1 Kittisak Sawanyawisuth2,3 1Department of Emergency Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, 2Department of Medicine, Faculty of Medicine, 3Research Center in Back, Neck, Other Joint Pain and Human Performance (BNOJPH), Khon Kaen University, Khon Kaen, Thailand Background: High-sensitivity troponin T (HS Trop T) plays an important role as a diagnostic marker for acute coronary syndrome. It is also related to cardiovascular outcomes. HS Trop T levels may be varied in individuals with renal dysfunction. This study aimed to find the appropriate HS Trop T cutoff points in chronic kidney disease (CKD) patients who had coronary artery occlusion. Patients and methods: The study was conducted at the Emergency Department, Ramathibodi Hospital, Mahidol University, Thailand. CKD patients stage 3–5 who had HS Trop T levels after 2 hours of chest pain and had coronary angiographic results were enrolled. Patients were divided into two groups: those who had significant occlusion of more than 70% of a coronary artery as the coronary artery disease (CAD) group and the non-CAD group. Results: In total, 210 patients met the study criteria. There were 132 patients (62.86%) who had significant stenosis of coronary arteries by coronary angiograms. The average age (standard deviation) of all patients was 71.02 (9.49) years. HS Trop T levels were significantly higher in all CKD patients with CAD than the non-CAD group (0.4973 versus 0.0384 ng/mL). Sex and HS Trop T levels were significantly associated with CAD by multivariate logistic regression analysis. The HS Trop T level of 0.041 ng/mL gave sensitivity and specificity of 65.91% and 75.65%, respectively, for CAD. Conclusion: The HS Trop T level of 0.041 ng/mL provided diagnostic properties for established coronary artery occlusion in CKD patients. Keywords: high-sensitivity troponin T, acute coronary syndrome, coronary artery occlusion, chronic kidney disease, sensitivity, specificity, coronary angiogram